Force-induced 1540 nm luminescence: Role of piezotronic effect in energy transfer process for mechanoluminescence - Li, Lejing; Wondraczek, Lothar; Peng, Mingying; Ma, Zhiwei; Zou, Bo (Nano Energy, 2020)
Smart materials which are capable of responding to external stimuli such as strain, temperature, electronic or magnetic fields have seen increasing demand from various fields of application. Mechanoluminescence (ML) is light emission phenomenon induced by external mechanical stimuli, which is often used to monitor and record the action of invisible forces in visible space. However, existing ML materials with limited spectral window has largely limited its applications. Extending ML operation to UV or near-infrared (NIR) regions would overcome this issue. In this work, materials with simultaneous visible to NIR ML is realized based on rare-earth (RE) ions doped CaZnOS, in particular, CaZnOS:Er3+ demonstrates ML on multiple spectral bands, including 510–538 nm, 538–570 nm, 640–680 nm, 845–880 nm, 960–1000 nm and 1450–1700 nm. Insight on the origin of ML in CaZnOS:RE3+ is discussed with the aid of in situ high-pressure studies. These observations indicate that the oriented migration of electrons which can be modulated or accelerated in a strain-induced piezoelectric field is a key in ML process. This interpretation provides a new tool for leveraging tailored ML performance in the further design of strain- and force-responsive materials.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Near infrared-II; Piezotronic effect; Smart materials; Stress visualization; Vis-NIR ML